Effects of tartrazine on proliferation and genetic damage in human lymphocytes. (13th June 2017) - Atlı Şekeroğlu, Zülal; Güneş, Büşra; Kontaş Yedier, Seval; Şekeroğlu, Vedat; Aydın, Birsen
Abstract: The color additive, tartrazine (TRZ), is widely used in food products, drugs and cosmetics. Genotoxicity of TRZ and its metabolites has not been investigated in detail in the presence and absence of a metabolic activator (S9 mix) in human. Therefore, the aim of this study is to investigate the cytotoxic and genotoxic effects of TRZ and its metabolites on cultured human lymphocytes by using chromosome aberration (CA) and micronucleus (MN) tests. Cultures were treated with 625, 1250 and 2500 μg/ml of TRZ in the presence and absence of S9 mix. TRZ showed cytotoxic activity at the highest concentration due to significant decrease in mitotic index (MI) in the absence of S9 mix when compared with solvent control. TRZ and metabolites significantly increased the CAs and aberrant cells in the presence and absence of S9 mix at the higher concentrations. Increased MN values in cultures with and without S9 mix were found to significantly at the highest concentration when tested. Our results indicated that while both TRZ and its metabolites have genotoxic potential on human lymphocyte cultures with and without S9 mix, TRZ can induce cytotoxicity at the highest concentration in culture without S9 mix under the experimental conditions.